2023
DOI: 10.1371/journal.pone.0274378
|View full text |Cite
|
Sign up to set email alerts
|

The Spanish version of the reflective functioning questionnaire: Validity data in the general population and individuals with personality disorders

Abstract: Introduction Mentalization or reflective functioning (RF) is the capacity to interpret oneself or the others in terms of internal mental states. Its failures have been linked to several mental disorders and interventions improving RF have a therapeutic effect. Mentalizing capacity of the parents influences the children’s attachment. The Reflective Functioning Questionnaire (RFQ-8) is a widely used tool for the assessment of RF. No instrument is available to assess general RF in Spanish-speaking samples. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 97 publications
1
10
0
Order By: Relevance
“… Outline of competing models of the latent structure of the RFQ-8 involving separate hyper- and hypomentalization factors (A) or (B) a single factor (hypomentalization). Correlated error terms for items 3 and 4 is based on prior studies (e.g., Ruiz-Parra et al, 2023 ). …”
Section: Resultsmentioning
confidence: 99%
“… Outline of competing models of the latent structure of the RFQ-8 involving separate hyper- and hypomentalization factors (A) or (B) a single factor (hypomentalization). Correlated error terms for items 3 and 4 is based on prior studies (e.g., Ruiz-Parra et al, 2023 ). …”
Section: Resultsmentioning
confidence: 99%
“…The RFQ-8 has been widely used in different populations and has been translated in many languages. Its psychometric properties have been evaluated in general population in English, French, Italian, Greek, German, Polish and Spanish; in clinical samples, e.g., in patients with personality disorders, and other psychiatric patients, in English, Italian, German and Spanish; and in type 1 diabetes adults in Greek [9,29,40,41,[44][45][46][47]. The two-factor structure of the original RFQ-8 was further confirmed by some of these studies, thereby substantiating the instrument's reliability and validity [29,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a change in scoring procedure was proposed, maintaining the scoring previously used in the RFQ design process (i.e., 1, 2, 3, 4, 5, 6, 7), except for item 7, reversely scored [ 40 , 41 ]. Moreover, further evidence based on exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) suggested that a one-factor model can sufficiently explain the observed covariation of the responses to RFQ-8 items when using this new way of scoring [ 40 , 41 , 46 , 47 ]. Aditionally, given that neither RFQ-8 certainty pole (using new proposed way of scoring), nor its certainty scale (using the previously proposed way of scoring) showed positive associations with indications of psychopathology when testing for U shape [ 40 , 41 ] or linear correlations [ 9 , 15 , 46 , 49 53 ], it has been suggested that the RFQ-8 can not sufficiently measure hypermentalization [ 41 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations